Intraspecific variation for heat stress tolerance in wild emmer-derived durum wheat populations - Balla, Mohammed Yousif; Kamal, Nasrein Mohamed; Tahir, Izzat Sidahmed Ali; Gorafi, Yasir Serag Alnor; Abdalla, Modather Galal Abdeldaim; Tsujimoto, Hisashi (Frontiers in Plant Science, 2025)
High temperatures pose a major threat to wheat productivity and necessitate the development of new cultivars that are resilient to future heat stress. Wild emmer (Triticum turgidum L. ssp. dicoccoides), which is a direct progenitor of domesticated durum wheat (Triticum turgidum L. ssp. durum) and contributor to the A and B genome of bread wheat (Triticum aestivum), offers a valuable genetic reservoir for developing climate-resilient wheat. However, the morphology of wild emmer is different from that of durum and bread wheat, in particular, the spikelets are fragile and naturally fall off, making it difficult to study its agronomic traits. In this study, we created nine backcrossed families between the popular durum wheat cultivar ‘Miki 3’ and nine wild emmer accessions collected from northern and southern lineages of this species. The objective was to investigate the intraspecific genetic variation in wild emmer and identify traits associated with heat stress tolerance. We evaluated these nine families under multi-environments ranging from optimum to severe heat stress conditions in Japan and Sudan and measured important agronomic traits. The result showed that two families, developed from accessions of both northern and southern lineages exhibited high harvest index, elevated chlorophyll content, and reduced canopy temperature under heat stress. Additionally, one family developed from an accession of the southern lineage displayed high biomass, harvest index, and seed number under heat-stress conditions. These three families produced high heat tolerant lines with unique introgressed segments from their wild emmer parents on chromosomes 1A, 2B, 5B, 6B, and 7B, which may be linked to heat resilience. From these results, we were able to identify significant intraspecific diversity between the wild emmer accessions in terms of heat stress tolerance. However, no significant tendency between the northern and southern lineages of wild emmer has been identified. These findings emphasize the need to harness not only the interspecific but also the intraspecific genetic variation of wild emmer diversity to uncover valuable genes for heat stress tolerance in wheat breeding programs.